2012
DOI: 10.2134/jeq2011.0122
|View full text |Cite
|
Sign up to set email alerts
|

Simple Biotoxicity Tests for Evaluation of Carbonaceous Soil Additives: Establishment and Reproducibility of Four Test Procedures

Abstract: Biochar derived from pyrolysis has received much attention recently as a soil additive to sequester carbon and increase soil fertility. Hydrochar, a brown, coal-like substance produced via hydrothermal carbonization, has also been suggested as a beneficial soil additive. However, before soil application, both types of char need to be tested for potential toxic effects. The aim of this study was to develop simple, inexpensive, and easy-to-apply test procedures to identify negative effects of chars but not to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
103
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(119 citation statements)
references
References 40 publications
(75 reference statements)
15
103
1
Order By: Relevance
“…The biochar was mixed with an inert, fine-sand medium and used in the salad germination test based on ISO 17126 (Busch et al, 2012), where the germination of a salt-sensitive species (Lactuca sativa L.) was evaluated. Several different proportions of biochar and fine sand were mixed following geometrical dilution.…”
Section: Salad Germination Testmentioning
confidence: 99%
See 1 more Smart Citation
“…The biochar was mixed with an inert, fine-sand medium and used in the salad germination test based on ISO 17126 (Busch et al, 2012), where the germination of a salt-sensitive species (Lactuca sativa L.) was evaluated. Several different proportions of biochar and fine sand were mixed following geometrical dilution.…”
Section: Salad Germination Testmentioning
confidence: 99%
“…In this study, we determined the chemical and physical properties of two biochars obtained from commercial vendors in Germany from different wastes: Biochar I (BC I) derived from wood chip and biochar II (BC II) derived from a blend of paper sludge and wheat husks and their properties are compared to those of biochar produced in Morocco from argan shells (ASBC). Therefore, we investigated the effects these three biochars have on (i) germination of salad (test for salt stress) and (ii) barley (test for toxic substances) and the findings are compared to those obtained from argan shells biochar (test procedures are adapted from Busch et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies focusing on soil-biochar-biota interactions in both terrestrial and aquatic ecosystems suggest potential impacts regarding the application of some biochars to soil on the activity and structure of edaphic and freshwater biological communities (due to leaching and potential transport of biochar particles into watercourse), their trophic relationships, and the processes they mediate. The extent and pattern of biological responses and/or observed toxicity can be assigned to bioavailable biochar fractions and appear to depend mainly on the target species and exposure scenarios, as well as on biochar physico-chemical properties and application rates (Busch et al 2012;Oleszczuk et al 2013;Smith et al 2012;Bastos et al 2014;Marks et al 2014;Domene et al 2015;Jaiswal et al 2015). A number of different mechanisms may play a role in determining biological responses to biochar amendment.…”
Section: Soil Biodiversity and Ecotoxicologymentioning
confidence: 99%
“…Expert opinion also concluded that various existing soil and aquatic biology and ecotoxicology indicators and methods may be suitable for evaluating soil-biochar-biota interactions, without requiring major adjustments or optimisation, besides possibly the recommended soil moisture content in standard testing (Busch et al 2012). It is also likely that methods relying on the use of biomarkers (e.g., DNA, RNA, PLFAs; proteomics) may require optimisation.…”
Section: Soil Biodiversity and Ecotoxicologymentioning
confidence: 99%
“…Biochar application to agricultural soil has recently been proposed as a feasible and effective win-win strategy to simultaneously improve soil water holding capacity [2],enhance soil fertility, decrease nutrient leaching and stimulate soil microbial activity [3], and thus increase crop productivity [4].…”
Section: Introductionmentioning
confidence: 99%